Dialog med ciljem in metodo - Ferbežar, Ina (Jezik in slovstvo, 2003)
The dialogue as a creative process of two or more participants is observed as a teaching method, while productive participation in a dialogue is viewed as one of the aims of language teaching. The paper seeks to explain why and how texts containing dialogues are used in the teaching and textbooks of Slovene as a second/foreign language, and offers a few suggestions for their more effective use. The inclusion of texts containing dialogues in Slovene second/foreign language textbooks is standard practice, but it has not yet been critically evaluated.
Keywords: Slovene; slovenščina; slovenščina kot drugi ali tuji jezik; didactic method; didaktika